2020
DOI: 10.3390/f11050555
|View full text |Cite
|
Sign up to set email alerts
|

Shrub Biomass Estimates in Former Burnt Areas Using Sentinel 2 Images Processing and Classification

Abstract: Shrubs growing in former burnt areas play two diametrically opposed roles. On the one hand, they protect the soil against erosion, promote rainwater infiltration, carbon sequestration and support animal life. On the other hand, after the shrubs’ density reaches a particular size for the canopy to touch and the shrubs’ biomass accumulates more than 10 Mg ha−1, they create the necessary conditions for severe wild fires to occur and spread. The creation of a methodology suitable to identify former burnt areas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…The models for forage crops included the additive and interactive effects of canopy cover. In forested habitats, the relationship between canopy cover and ground vegetation biomass was positive for shrubs but negative for grass, consistent with Aranha et al (2020), who reported that canopy closure is positively correlated with shrub biomass because photosynthetic capacity is more strongly related to canopy cover (Kaur 2007;Moreno-de las Heraset al, 2015). Canopy cover was a strong (negative) predictor of grass biomass; increasing canopy cover significantly reduced grass (Randle, 2018).…”
Section: Spatial Prediction Modelssupporting
confidence: 83%
“…The models for forage crops included the additive and interactive effects of canopy cover. In forested habitats, the relationship between canopy cover and ground vegetation biomass was positive for shrubs but negative for grass, consistent with Aranha et al (2020), who reported that canopy closure is positively correlated with shrub biomass because photosynthetic capacity is more strongly related to canopy cover (Kaur 2007;Moreno-de las Heraset al, 2015). Canopy cover was a strong (negative) predictor of grass biomass; increasing canopy cover significantly reduced grass (Randle, 2018).…”
Section: Spatial Prediction Modelssupporting
confidence: 83%
“…The model developed by [26] registered a general accuracy higher than 90%, but because it is a model based on pre-established limits according to the spectral characteristics of the area analysed, this accuracy can change according to the study area. Concerning the models for detecting changes applied in Portugal, one can find the works of [42] to estimate the increase in vegetation biomass after fires in the north of the country, where the overall accuracy of 79.6% was recorded and of [31], in the search for vegetation cuts around the road network which yielded an accuracy of 79% for an annual temporal cut-off and 98% for a monthly temporal cut-off.…”
Section: Resultsmentioning
confidence: 99%
“…Next, mosaicking, clipping, band calculation, and other processing methods were carried out using Envi v5.3. Of these, SNAP is a remote sensing image processing software developed by the European Space Agency, which is mainly used to process sentinel data [49].…”
Section: Pre-processingmentioning
confidence: 99%